2018
DOI: 10.31016/1998-8435-2018-12-3-33-41
|View full text |Cite
|
Sign up to set email alerts
|

Hydatidosis of Camels and Sheep Slaughtered in Aswan Governorate, Southern Egypt

Abstract: Background: Hydatidosis is an infection caused by the cystic larval stage of Echinococcus granulosus. This disease is a zoonotic disease has a worldwide distribution and common in developing and undeveloped countries. Objectives: The objective of the present study is to studying the infection rate and predilection seats of hydatid cyst affections among slaughtered food animals in Aswan Governorate, southern Egypt and study the effect of age and sex of infected slaughtered animals on the infection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…According to its detrimental effect on ruminant health and wellbeing, gastrointestinal parasitism is a global problem that is limiting ruminant efficiency (Dyab et al, 2018;Paul et al, 2020;Abdelhamid et al, 2021). Infections of ruminant livestock with paramphistomes have become more common and are still widespread.…”
Section: Resultsmentioning
confidence: 99%
“…According to its detrimental effect on ruminant health and wellbeing, gastrointestinal parasitism is a global problem that is limiting ruminant efficiency (Dyab et al, 2018;Paul et al, 2020;Abdelhamid et al, 2021). Infections of ruminant livestock with paramphistomes have become more common and are still widespread.…”
Section: Resultsmentioning
confidence: 99%
“…Bahnass (2009) in Zagazig (Egypt), who detected in liver and lung with percentage of 9.02 % and 90.9 % respectively. Dyab et al (2018) in Aswan (Egypt), studied the cystic hydatidosis in 8.32% mostly found in camel lung. Hence it is clear that the most of the previous authors reported the lungs as the preferred location of hydatid cyst in camels.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) Elminia Cattle/Buffaloes 120/50 6 (5.0)/2 (4.0) Lung, liver Dyab et al (2019) Assiut Camels 200 12 (6.0) Liver, lung, kidney Dyab et al (2017) Sheep 250 (2.4) na Taher & Sayed (2011) Goats 90 6 (6.7) Liver Abdelazeem et al (2020) New valley Sheep 459 37 (8.1) Liver, lung, kidney Osman et al (2014) Goats 528 29 (5.5) Red Sea, Qena, Sohag, Aswan Sheep 820 58 (14.1) Lung, liver, viscera Omar et al. (2013) Goats 130 17 (13.1) Camels 240 12 (5.0) Cattle 2910 2 (0.1) Buffaloes 398 0 (0) Aswan Camels/Sheep 2080/674 173 (8.3)/3 (0.54) Lung, liver Dyab et al (2018) …”
Section: Studies On Cystic Echinococcosis In Egyptmentioning
confidence: 99%
“…In a systematic analysis of the global risk factors for hydatid disease in livestock, several factors including locations, host species, age, sex, seasonal variations, and environmental factors were associated with the diseases burden ( Otero-Abad & Torgerson, 2013 ). In Egyptian livestock, age, sex and season have been associated with high prevalence of CE in camels and sheep ( Dyab et al., 2018a ; Ahmed et al., 2021 ). Female camels, for example, were more susceptible to CE infection than male camels possibly because of the slaughtering of female camels at an older age, as they are maintained for reproduction ( Dyab et al., 2018a ).…”
Section: Risk Factors Associated With Ce In Egyptmentioning
confidence: 99%
See 1 more Smart Citation